Time-space Characteristic of Interruptible Load on Dispatch Solution. Issue 28 (2015) - Yao, Shuangchen; Liu, Haoming; Lu, Dan; Yuan, Xiaoling
Abstract: The interruptible load is effective to alleviate the tight power supply. In this paper, an optimization model is developed for power company to determine the industrial load participating in peak scheduling, and the time-space characteristic of interruptible load is discussed, including the refinement of minimum load capacity and power interruption duration. A test on simple case is carried out, and the results show that the more spatial and temporal refined interruptible load can guarantee for peak load shifting and reduce the surplus scheduling load. In addition, compensation cost is also cut down, as well as the user's satisfaction improved.